Alternative impression technique for edentulous anterior maxillary flabby tissue (Research, Society and Development, 2020)
This present study describes an impression technique to rehabilitate patients with flabby ridge in pre-maxilla through complete dentures. The proposed technique consists on the association of nondisplacive impression of the flabby area in the primary and functional impression. Therefore, a primary impression was performed with irreversible hydrocolloid with a dual impression. The impression material was removed at the region corresponding to the flabby area, characterizing a window, where a re-impression was conducted with the same material in a more fluid consistency. The functional impression was executed with a custom tray with perforations at the flabby area fabricated over a primary anatomic cast previously relieved. As a result, an anatomic impression with reduced compression over the flabby ridge was obtained. Moreover, an accentuated decrease of the mucosa compression was obtained through the material overflow from the custom tray perforations at the functional impression. After the acrylization of the prosthetic piece, a delimited box corresponding to the flabby mucosa in the prosthesis base was verified. Thus, it is concluded that the association of techniques proposed in this study reduced the compression over the flabby ridge area resulting in a complete denture copying anatomically the flabby area at rest. Thereby, in this case through a precise negative reproduction, a more favorable retention of the maxillary complete denture was obtained in patients with flabby ridge at the pre-maxillary area.